International Legislation on Money Laundering - Cvetković, Dragan M.; Davidović, Dušan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2013)
As a special form of organized transnational crime, with a high degree of social danger, money laundering is becoming a serious international problem. It is therefore quite justified to include the international community in combating this criminal phenomenon on a global scale. Increased interest of the international community to combat this phenomenon has resulted in the adoption of certain international laws and international development organizations. A key element in the fight against money laundering and terrorist financing is the need for systems to prevent money laundering in individual countries and monitor evolving international standards. Given that money laundering threatens the vital values within a state, but also internationally, all countries are interested in combating these negative phenomena in society, and are described in numerous international scientific conferences devoted to this subject. The global scale of money laundering can not be deleted at once, or activities at the individual level, but through cooperation and unification of legislation and regulatory measures at the international level.